Integrasi Pembelajaran Budaya Jepang dalam Pengajaran Bahasa Indonesia bagi Penutur Asing (BIPA) - Salsabila, Rona Atira; Safithri, Shabrina Awwaliyah; Huda, Ahmad Ulil; Chamidah, Dewi Chamidah (LPPM STKIP PGRI Bandar Lampung, 2024)
In the current era of development, learning BIPA (Indonesian for Foreign Speakers) is of great interest to many people because BIPA is not just about language learning, but also about cultural understanding and integration. This research explains the influence of Japanese culture in teaching BIPA and the challenges in teaching BIPA, because every learning is inseparable from the challenges faced. This research uses a qualitative approach with literature study as the research design. The results of this study indicate that the integration of cultural elements in the teaching of BIPA is urgent. This is due to the significant differences in cultural characteristics. In addition, the process of cultural integration in BIPA teaching is not free from challenges. One of the main challenges is the difference in cultural background that can affect the way learners absorb and understand teaching materials. It can be concluded that the integration of cultural learning in BIPA is one of the important efforts in improving the effectiveness of language teaching and introducing Indonesian culture to the international community.